The roles of ING5 in cancer: A tumor suppressor - Zheng, Hua-chuan; Xue, Hang; Jiang, Hua-mao (Frontiers in Cell and Developmental Biology, 2022)
As a Class II tumor suppressor, ING5 contains nuclear localization signal, plant homeodomain, novel conserved region, and leucine zipper-like domains. ING5 proteins form homodimer into a coil-coil structure, and heterodimers with ING4, histone H3K4me3, histone acetyltransferase (HAT) complex, Tip60, Cyclin A1/CDK2, INCA1 and EBNA3C for the transcription of target genes. The acetylated proteins up-regulated by ING5 are preferentially located in nucleus and act as transcription cofactors, chromatin and DNA binding functions, while those down-regulated by ING5 mostly in cytoplasm and contribute to metabolism. ING5 promotes the autoacetylation of HAT p300, p53, histone H3 and H4 for the transcription of downstream genes (Bax, GADD45, p21, p27 and so forth). Transcriptionally, YY1 and SRF up-regulate ING5 mRNA expression by the interaction of YY1-SRF-p53-ING5 complex with ING5 promoter. Translationally, ING5 is targeted by miR-196, miR-196a, miR-196b-5p, miR-193a-3p, miR-27-3p, miR-200b/200a/429, miR-1307, miR-193, miR-222, miR-331-3p, miR-181b, miR-543 and miR-196-b. ING5 suppresses proliferation, migration, invasion and tumor growth of various cancer cells via the suppression of EGFR/PI3K/Akt, IL-6/STAT3, Akt/NF-κB/NF-κB/MMP-9 or IL-6/CXCL12 pathway. ING5-mediated chemoresistance is closely linked to anti-apoptosis, overexpression of chemoresistant genes, the activation of PI3K/Akt/NF-κB and Wnt/β-catenin signal pathways. Histologically, ING5 abrogation in gastric stem-like and pdx1-positive cells causes gastric dysplasia and cancer, and conditional ING5 knockout in pdx1-positive and gastric chief cells increases MNU-induced gastric carcinogenesis. Intestinal ING5 deletion increases AOM/DSS- induced colorectal carcinogenesis and decreases high-fat-diet weight. The overexpression and nucleocytoplasmic translocation of ING5 are seen during carcinogenesis, and ING5 expression was inversely associated with aggressive behaviors and poor prognosis in a variety of cancers. These findings indicated that ING5 might be used for a molecular marker for carcinogenesis and following progression, and as a target for gene therapy if its chemoresistant function might be ameliorated.